Implementation of Deep Learning in Improving Islamic Religious Education and Character Education - Andini, Riddo; Fitri, Anisya; Hafizah, Fitri; Hayat, Fauzan; Ramadhan, Iqwanul; Ikrar, Muhammad (Ahlussunnah: Journal of Islamic Education, 2025)
Islamic Religious Education and Ethics in the era of the 4.0 industrial revolution and 5.0 society face complex challenges between the transmission of authentic Islamic teachings and the need for creativity, collaboration, critical thinking, and digital literacy. The conventional approach that emphasizes memorization often fails to shape a strong spiritual character. Deep Learning, as part of artificial intelligence, is introduced as a solution with the principles of mindful, meaningful, and joyful learning. This approach is in line with the Merdeka Curriculum, which emphasizes active student participation and the integration of technology for 21st-century skills. This study examines the implementation of Deep Learning in junior high schools through observation, interviews with Islamic Education teachers, and documentation. The results show that constructivist-based lesson plan (RPP) planning encourages students to construct a deep and applicable understanding of religious teachings. The implementation of Deep Learning principles, such as reflective discussions and hands-on practices (e.g., qurbani sacrifice), enhances spiritual awareness, internalization of values, and application in real life. Despite challenges such as time constraints, this approach has the potential to create a religious and adaptive golden generation in 2045.